The repercussions of changing the personal status law on the increase in family lawsuits (Divorce and Khul' lawsuits as a model) - Allam, Abdelfattah Lotfi; Farah, Muhammad Saeid; Al-Khawaja, Muhammad Yasser; Elmesalamy, Marwa (Journal of Language, Literature, Social and Cultural Studies, 2023)
The current research dealt with the study of the impact of changing the Personal Status Law on the number of family lawsuits "divorce and divorce lawsuits as a model", by monitoring thirty years, which is the period from 1990 to 2020 depending on the data of the Central Agency for Public Mobilization and Statistics through the annual bulletin Marriage and divorce, as this period indicates the change of the Personal Status Law for more than five amendments between a total amendment to the law, and a partial amendment of some articles, and the current study has found a relationship between Changing the Personal Status Law and between the increasing number of family lawsuits, as divorce and divorce lawsuits increased during the study period affected by the change in the Personal Status Law during that period, which necessitates the need for deliberation in amending personal status laws to take into account the preservation of the family entity from disintegration.